2015
DOI: 10.1186/s40658-015-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of injection dose, post-reconstruction filtering, and collimator choice on image quality of myocardial perfusion SPECT using cadmium-zinc telluride detectors in the rat

Abstract: BackgroundThe aims of this study were (1) to evaluate the impact of injection dose, post-reconstruction filtering, and collimator choice on image quality of myocardial perfusion single-photon emission computed tomography (SPECT) using cadmium-zinc telluride (CZT) detectors and (2) to determine how these factors affect measured infarct size in the in vivo rat.MethodsTwenty-four healthy and eight myocardial infarct (MI) rats underwent myocardial perfusion SPECT imaging after injection of various doses (25 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A SPECT system with cadmium-zinc telluride detectors and two different five-pinhole collimators was used (sensitivity = 321 cps/MBq, 139 cps/MBq; resolution = 1.5 mm, 1.2 mm). The evaluation by two readers showed an increase in image quality by higher injection dose (25–200 MBq) and stronger filters (no filter; FWHM = 1.5 mm, 2.5 mm) 14 . The injection dose had more impact on the image quality score than we found for the scan time, but the results are still largely consistent with ours.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A SPECT system with cadmium-zinc telluride detectors and two different five-pinhole collimators was used (sensitivity = 321 cps/MBq, 139 cps/MBq; resolution = 1.5 mm, 1.2 mm). The evaluation by two readers showed an increase in image quality by higher injection dose (25–200 MBq) and stronger filters (no filter; FWHM = 1.5 mm, 2.5 mm) 14 . The injection dose had more impact on the image quality score than we found for the scan time, but the results are still largely consistent with ours.…”
Section: Discussionmentioning
confidence: 97%
“…High spatial resolution can improve the diagnostic value of SPECT scans if sufficient image quality is achieved, which is particularly affected by the choice of collimator 12 , reconstruction algorithm 5 , 13 , post-reconstruction filter 13 and injection dose 14 . Hence, we evaluated the influence of acquisition time and Gaussian post-filtering, using a novel iterative reconstruction algorithm with similarity-regulated ordered-subsets expectation maximization (SROSEM), that enables constant reconstruction parameters for a wide range of activity concentrations 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these authors reported an unexpected relatively low perfusion in the distal segments of the lateral wall (10). There is no mention to such feature in a later study on the optimization of injected activity and reconstruction parameters in male Wistar rats imaged with 99m Tc-tetrofosmin using cadmium–zinc telluride detectors (25). …”
Section: Measurement Of Cardiac Perfusionmentioning
confidence: 99%
“…Therefore there is no accordance between authors concerning the best Fc for Butterworth filter in SPECT imaging [6,7]. It is suggested that the Fc should be determined by referring to the total counts in each examination [8,9]. For high count images, a higher Fc is preferred to optimize the reconstruction process of an image.…”
Section: Introductionmentioning
confidence: 99%